PENGARUH EDUKASI GIZI TERHADAP PEMAHAMAN ISI PIRINGKU PADA SISWA MI 1 JELUN: THE EFFECT OF NUTRITION EDUCATION ON UNDERSTANDING OF THE ISI PIRINGKU IN STUDENTS OF MI 1 JELUN - Arsila Khabibi; Nazwa Aulia; Syarifa Gadis Venaprilla; Septa Indra Puspikawati (Jurnal Gizi Masyarakat Indonesia (The Journal of Indonesian Community Nutrition), 2026)
Introduction: Indonesia still faces complex nutritional problems, one of which is caused by the low public understanding of balanced nutrition. Elementary school children, especially grades 3 and 4, are a vulnerable group that requires educational interventions to shape healthy eating behaviors. The concept of "Isi Piringku" was introduced as a guideline for balanced nutrition, but students' understanding of this concept is still low, especially in rural areas. Method: The study used a quasi-experimental design with a pretest and posttest approach in one group. The intervention was implemented through the "Si Piring Pintar dan Teman-Teman Gizi" activity which combines visual media (powerpoint, food miniatures) and interactive games based on SCT principles. Participants consisted of 19 grades 3 and 4 of MI 1 Jelun. Then the data were analyzed using a paired sample t-test after ensuring data normality with the Shapiro-Wilk test. Results: This study demonstrated a significant increase in students' understanding with a p-value of 0.000 (<0.05) and a mean difference between pre-test and post-test scores of 26.32 (95% CI: 18.91–33.72). In addition to cognitive aspects, students also demonstrated improved practical skills in applying the "Isi Piringku" concept through group games and simulations. Conclusion: An educational intervention based on SCT effectively improved the understanding of the concept of "Isi Piringku" (My Plate Contents) in grades 3 and 4 of MI 1 Jelun. This was demonstrated by a significant increase in pretest and posttest scores (p < 0.05). The SCT approach, through observation, direct experience, and interactive media, helped students understand the concept of balanced nutrition and apply it in learning activities. These findings indicate that the SCT approach has the potential to be an effective strategy in nutrition education for elementary school students.